Verso la neutralità climatica di architetture e città green Sperimentazioni e casi di studio nel Sud Europa e in area mediterranea - Tucci, Fabrizio (Architettura e Innovazione. Built Environment Technologies and Healthy Architectures, 2023)
Regenerating and transforming urban areas and cities into resilient, sustainable, and flexible organisms represent the key conditions for sustainable, resilient, and no longer postponable planning. The ongoing debate, which involves political authorities and civil society, raises the need to act by changing the vision of the quality of living towards actions of regeneration and redevelopment of urban, intermediate and proximity spaces in order to promote social integration and support local micro-activities: in this sense the need to intervene on the connective aspects, on the bioclimatic and energetic behavior of building aggregates capable of adapting to increasingly frequent climate changes becomes crucial. The quality of living in these urban spaces defines a strategic importance to incentivize solutions and good practices for the mitigation of climate change, with targeted actions for the decarbonization of anthropic processes. The objectives, set by law, of a 55% reduction in greenhouse gas emissions by 2030 compared to 1990 levels and the achievement of net zero GHG emissions in 2050 are still far away today, also considering a rather weak response coming from the latest Conferences of the Parties (COP). The careful and targeted selection of case studies proposed in this book, the result of intense research activity still underway, derives from a larger research carried out in the European framework of urban district and eco-neighborhood projects for the construction of the Verso report the climate neutrality of green cities: the result is a final selection of over thirty case studies in Southern Europe and the Mediterranean area, which work on the systematization of the six thematic axes such as energy transition, bioclimatic effectiveness, circularity of resources, functional mix, sustainable mobility and green and gray CO2 subtraction. These become the milestones for analyzing neighbourhoods, districts and cities created and in progress, as they illustrate the improvements achieved in terms of reducing carbon emissions within the individual technological-environmental solutions found, with the aim of defining new protocols for responsible and sustainable development, interscalar and multidisciplinary.